Effective removal of hypnotic drug from the aqueous medium through adsorption on graphene oxide magnetic derivatives (2024)
This study evaluated the adsorption of zolpidem (ZPD) on magnetic graphene oxide (GO‧Fe3O4). The graphene oxide-based magnetic adsorbents used to remove zolpidem were synthesized with different amounts of magnetite. The Adsorbents were characterized, confirming the presence of magnetic nanoparticles on the graphene oxide surface. The best magnetic nanoadsorbent was GO‧Fe3O4 1:1, with a removal percentage of 87.07 % at pH 5.0 and 293.15 K. In this sense, zolpidem removal was unrelated to the graphene oxide surface area but to the surface chemistry of the adsorbent. The physical–chemical Interactions between the ZPD molecules and the functional groups of the adsorbent were suggested. ZPD adsorption on GO‧Fe3O4 1:1 was spontaneous and exothermic. The equilibrium and kinetic studies (Sips and Elovich) suggested adsorption in a heterogeneous surface. Furthermore, the adsorbent presented excellent adsorption efficiency even after many regeneration cycles, and magnetic behavior avoids the centrifugation/filtration steps. Until now, no study in the literature reported removing this harmful and widespread hypnotic drug from water contamination, and GO·Fe3O4 1:1 was an efficient nanomaterial to remove ZPD from aqueous solutions.